Single-port laparoscopic Deloyers procedure for tension-free anastomosis after extended left colectomy or subtotal colectomy: A 6-patient case series. Issue 31 (31st July 2020) - Choi, Byung Jo; Kwon, Woojin; Baek, So Hye; Jeong, Won Jun; Lee, Sang Chul
Abstract : Abstract: Right colon-to-rectal anastomosis is performed in relatively rare conditions, including after subtotal colectomy or extended left hemicolectomy. One technique of tension-free anastomosis is the Deloyers procedure that includes cranio-caudal rotation of the right colon. As with other colon surgeries, the laparoscopic approach has been adapted for the Deloyers procedure. Nevertheless, due to its rare indications and technical specificity, only a small case series have been reported. Here, we report our experience with single-port laparoscopic (SPL) Deloyers procedures. Between June 2013 and March 2018, 6 patients underwent SPL Deloyers procedures. Three patients underwent SPL subtotal colectomy with ascending colon-to-rectal anastomosis for sigmoid colon cancer with chronic ischemic colitis, sigmoid colon cancer with left colon ischemia, and synchronous transverse and sigmoid colon cancer, respectively. The other 3 patients underwent SPL Hartmann reversal using the Deloyers procedure technique for 2 transverse colon end colostomies and 1 ascending colon end colostomy state, which were the result of a previous extended left hemicolectomy and subtotal colectomy, respectively. A commercially available single port was used with conventional straight and rigid laparoscopic instruments. The surgical procedures were similar to those performed during conventional laparoscopic surgery. For the anastomosis, the mobilized remaining ascending colon was rotated 180° counter-clockwise around the axis of the ileocolic pedicle. Tension-free colorectal anastomosis was then performed between the well-vascularized ascending colon and the rectal stump. The SPL Deloyers procedure was successful in all patients. No additional incisions for trocars or conversions to open surgery were necessary. The operative time and postoperative length of stay were 210 to 470 min and 8 to 21 days, respectively. No intraoperative complications were noted. There were 3 minor postoperative complications without anastomotic leakage. All patients had 2 to 3 bowel movements per day, and 1 patient regularly took loperamide at 6 months after surgery. The SPL Deloyers procedure was feasible and allowed patients to achieve good bowel movements. This operation may be considered an additional surgical option for experienced SPL surgeons in selected patients.